Resenha crítica de filmes com o eixo temático preconceito racial : uma proposta pedagógica para o desenvolvimento da competência argumentativa - Lima, Walneyde de Santana (2018)
Being aware that Portuguse Language teaching should focus on the student’s preparation for the effective use of the language in his/her social practices, teaching text production should become a priority in order to lead the student to interact socially through language. Following this assumption, the present research brings a classroom experience focused on the production of the textual genre critical review starting out with the national films, Branco sai, preto fica ― White leaves, black stands (feature- lenth film); A negação do Brasil―Denial of Brazil (documentary); O dia de Jerusa― Jerusa’s day (short-lenth film) and an American feature-lenth film 42- the true story of an American Legend, which bring the racial prejudice as theme. The research participants are ninth grade students from a municipal publc fundamental school located in the city of Aracaju – Sergipe, Brazil, in 2017. We intended to know how the written production can contribute to the students’ improvement upon their argumentative competence since the criticism is the base of this genre and the chosen theme also asks for a well-defined point of view. The methodology followed action research guidelines from a qualitative approach. The research tools included questionairs, classroom dynamics observations, theoretical and films reading and the analysis of the students’ text production, based on studies about the genre and argumentation. Besides being widely used in the academic field, critical review has a guaranteed space in media such as newspapers and magazines, and becomes very important,not only for developing skills as describing and summarizing but also for being an excellent opportunity to critical reflections on the films that were reviewed. Considering cinema as art and entertainment, it is admitted as a resource which lead to a socio-cultural formation, since it is a source of culture and knowledge. In order to support our research, we have based it on Bakhtin (2010), Fiorin (2016), Ferreira (2010), Andrade (2006), Machado (1996), Marcuschi (2008, 2010, 2011), Antunes (2009), Bazerman (2011), Rodrigues (2005), Rojo (2005, 2008, 2015), Meyer (2008), Chaim Perelmam e Tyteca (1996) and the Parâmentros Curriculares Nacionais (National Curricular Standards), among others.